Analisis Du Pont System dalam Menilai Kinerja Keuangan pada PT Telkom Indonesia (Persero) Tbk, PT Indosat Tbk, PT Xl Axiata Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2017–2021 - Keban, Hilaria Rosdiana; Man, Stanis; Seran, Paskalis; Manafe, Henny A.; Bibiana, Rere Paulina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this research is to analyze the assessment of the level of financial performance at PT Telkom Indonesia (Persero) Tbk, using the Du Pont System analysis method for the 2017–2021 period, to analyze the assessment of the level of financial performance at PT Indosat Tbk, using the Du Pont System analysis method for the 2017 period –2021, and to analyze the assessment of the level of financial performance at PT XL Axiata Tbk, using the Du Pont System analysis method for the 2017–2021 period. The type of data used in this research is quantitative data. The research results show that the financial performance of telecommunications companies listed on the Indonesia Stock Exchange as measured by Du Pont System analysis during the research period was still in poor condition. This was caused by sales and profits after tax decreasing. Likewise, total assets turnover decreased, this was caused by a decrease in sales value and total asset value. Return on investment belonging to telecommunications companies listed on the Indonesia Stock Exchange during the 2017-2021 period experienced a decline. This was caused by a decrease in the value of net profit margin and total assets turnover in that period.